Logistics Management and World Seaborne Trade. - Muthiah, Krishna Veni (Himalaya Pub. House, 2010)
This present book envisages to bring about an understanding of the strategic importance of logistics management, a fundamental knowledge about the world shipping industry of large, and a tracing of the technological development in international transportation.